Creating Instagram Feeds as Arts and Culture Weeks Promotional Media with Canva Application and EPIC Method - Devyanti, Kharisma Nur; Faylasuf, Hafiz Fadli; Zahir, Rafi Hilal; Fami, Amata; Wahyoedi, Bontisesari (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
This study aimed to develop an engaging Instagram feed design to enhance visitor participation at the Cultural Arts Week event. The research employed a case study method with a qualitative approach. The sample consisted of 16 respondents, including the chief executive of Cultural Arts Week, 2 computer experts, 2 graphic design experts, and 11 visitors to the event, all of whom were students at the IPB Vocational School. The effectiveness of the design was assessed using the EPIC method, which evaluates Empathy, Persuasion, Impact, and Communication. The results indicated a score of 4.25 for Empathy, 4.1 for Persuasion, 4.12 for Impact, and 4.27 for Communication, yielding an overall EPIC Rate of 4.18.